Nb-Doped MXene With Enhanced Energy Storage Capacity and Stability - Fatima, Mahjabeen; Fatheema, Jameela; Monir, Nasbah B.; Siddique, Ahmad Hassan; Khan, Bushra; Islam, Amjad; Akinwande, Deji; Rizwan, Syed (Frontiers in Chemistry, 2020)
MXenes present unique features as materials for energy storage; however, limited interlayer distance, and structural stability with ongoing cycling limit their applications. Here, we have developed a unique method involving incorporating Nb atoms into MXene (Ti3C2) to enhance its ability to achieve higher ionic storage and longer stability. Computational analysis using density functional theory was performed that explained the material structure, electronic structure, band structure, and density of states in atomistic detail. Nb-doped MXene showed a good charge storage capacity of 442.7 F/g, which makes it applicable in a supercapacitor. X-ray diffraction (XRD) indicated c-lattice parameter enhancement after Nb-doping in MXene (from 19.2A° to 23.4A°), which showed the effect of the introduction of an element with a larger ionic radius (Nb). Also, the bandgap changes from 0.9 eV for pristine MXene to 0.1 eV for Nb-doped MXene, which indicates that the latter has the signature of increased conductivity due to more metallic nature, in support of the experimental results. This work presents not only the effect of doping in MXene but also helps to explain the phenomena involved in changes in physical parameters, advancing the field of energy storage based on 2D materials.